Stochastic-process hybrid filtration on observation with memory in the presence of anomalous interference\; Automatic Control and Computer Sciences; Vol. 34, Iss. 2 - Dyomin N. S. Nikolas S. (2000, 2000)
Optimality is considered in the elimination of anomalous components from the observation vector in the case of the filter synthesized in [1], together with the dependence of the estimation error on the ways in which the anomalous interference components influence the observation vector ones.